Ortho Evra ™/Evra ™ versus oral contraceptives: follicular development and ovulation in normal cycles and after an intentional dosing error - Pierson, Roger A; Archer, David F; Moreau, Michèle; Shangold, Gary A; Fisher, Alan C; Creasy, George W (Fertility and sterility, 2003)
To compare the effects of the contraceptive patch to oral contraceptives (OCs) on follicular size and incidence of ovulation in normal cycles and after dosing errors. Randomized, open-label. Twelve centers. One hundred twenty-four ovulatory women. Subjects received either the patch (groups 1 and 2) or one of three OCs. Correct dosing occurred in cycles 1, 2, 3, and 5. The following dosing errors were planned during cycle 4, a shortened 10-day cycle: [1] patch group 1 subjects wore one patch for 10 consecutive days; [2] for patch group 2 and OC subjects, 7 dosing days were followed by 3 drug-free days. Follicular size, as determined at each cycle by the maximum mean follicular diameter. After a 3-day dosing error, follicular size was significantly smaller in the patch group (mean, 7.0 mm) vs. each OC group (range of means, 11.8–17.1 mm). Similar results were seen after proper dosing. The incidence of ovulation was significantly lower for the patch users than for women using OCs. Follicular size and incidence of ovulation were significantly reduced among contraceptive patch users compared with women using OCs in normal cycles and after planned dosing errors.